2021
DOI: 10.1128/spectrum.00291-21
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Vaccine Positivity of SARS-CoV-2 Antibodies in Alberta, Canada during the First Two Waves of the COVID-19 Pandemic

Abstract: Using SARS-CoV-2 serology testing, we assessed the proportion of people in Alberta, Canada (population 4.4 million) positive for COVID-19 antibodies, indicating previous infection, during the first two waves of the COVID-19 pandemic (prior to vaccination programs). Linking these results with sociodemographic population data provides valuable information as to which groups of the population are more likely to have been infected with the SARS-CoV-2 virus to help facilitate public health decision-making and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“… 20 23 A study from Alberta conducted from June 2020 to January 2021 reported a high seropositivity of 19.8%, which reflected an outbreak in a large meat-packing plant. 21 Higher seropositivity of two-to threefold has also been reported in ethnic minority groups, including Black and South Asian people, compared with white people living in the United Kingdom (1 reference from preprint), 22 , 23 and comparing essential with nonessential workers in Toronto, Canada. 20 Compared with population-based seroprevalence studies conducted during the third wave of the pandemic in Canada, such as a report by Canadian Blood Services showing a seropositivity for previous infection of 3.95%, 24 we observed a relatively high rate of seropositivity among South Asian people in the GTA (23.6%).…”
Section: Discussionmentioning
confidence: 99%
“… 20 23 A study from Alberta conducted from June 2020 to January 2021 reported a high seropositivity of 19.8%, which reflected an outbreak in a large meat-packing plant. 21 Higher seropositivity of two-to threefold has also been reported in ethnic minority groups, including Black and South Asian people, compared with white people living in the United Kingdom (1 reference from preprint), 22 , 23 and comparing essential with nonessential workers in Toronto, Canada. 20 Compared with population-based seroprevalence studies conducted during the third wave of the pandemic in Canada, such as a report by Canadian Blood Services showing a seropositivity for previous infection of 3.95%, 24 we observed a relatively high rate of seropositivity among South Asian people in the GTA (23.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Seropositivity for SARS-CoV-2 nucleocapsid antibodies was found in 1% of individuals with IBD. In contrast, seropositivity in the general population in Calgary during the same time period was 1.8%, suggesting that patients with IBD were less exposed to SARS-CoV-2 or that serological response postinfection was not as robust as the general population 3…”
mentioning
confidence: 83%
“…To date we have published one report from our study that described seroprevalence in the first wave of the pandemic ( 7 ). Other Canadian serosurveys have been carried out over limited time periods and relied on blood spots for serology ( 11 , 12 ) or have been limited to specific regions ( 13 , 14 ) and/or populations ( 15 17 ). In other countries, such as the United States, blood donors are central to national monitoring of infections and vaccine seroprevalence ( 5 , 18 ) but have not published data on vaccine-related antibody concentrations.…”
Section: Introductionmentioning
confidence: 99%